Research Of Operational Reliability Of Automatic Transmissions - Turakulov Bahtiyor H; Ibrahimov Karimjon I (Zien Journals, 2022)
This article is devoted to the review of existing designs of automatic gearbox (AG). Based on the analysis, three types of AG systems are identified, which are installed in modern designs of cars and trucks, as well as in buses. The article presents the main advantages and disadvantages of various types of AG. The regularities of the distribution of the failure density depending on the mileage of city buses are shown. Based on the analytical review, it was found that the failure densities of various types of AG are in good agreement with the logarithmic-normal distribution and the Weibull-Gnedenko distribution law.
Keywords: Automatic; manual transmission; reliability; torque converter